1993
DOI: 10.1111/j.2042-7158.1993.tb07088.x
|View full text |Cite
|
Sign up to set email alerts
|

Solubility, Stability and Ionization Behaviour of Famotidine

Abstract: The pKa of famotidine was determined at 23 +/- 0.2 degrees C to be 6.76, 6.98 and 6.89 by a spectrophotometric, solubility, and partitioning method, respectively. The pH-solubility profile of famotidine indicated an intrinsic solubility of 2.7 mM at 23 degrees C. Degradation of famotidine followed pseudo-first-order kinetics over a pH range of 1-11 at 37 +/- 0.2 degrees C and at an ionic strength (mu) of 0.5. The pH-rate profile was accounted for by the specific acid and base catalysed reactions as well as wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 16 publications
(8 reference statements)
1
23
0
Order By: Relevance
“…Keeping in mind that in cyclic voltammetry the highest peak currents corresponding to the famotidine oxidation on PGE were obtained in ABS pH 4.06 and PBS pH 6.81 and due to the fact that famotidine maximum stability was reported to be at pH 6.30, 33 for further studies PBS pH 6.81 was selected as supporting electrolyte.…”
Section: Electrochemical Behavior Of Famotidinementioning
confidence: 99%
“…Keeping in mind that in cyclic voltammetry the highest peak currents corresponding to the famotidine oxidation on PGE were obtained in ABS pH 4.06 and PBS pH 6.81 and due to the fact that famotidine maximum stability was reported to be at pH 6.30, 33 for further studies PBS pH 6.81 was selected as supporting electrolyte.…”
Section: Electrochemical Behavior Of Famotidinementioning
confidence: 99%
“…It has been reported that poor lipophilicity, poor aqueous solubility and susceptibility to gastric degradation may contribute to the low and variable oral bioavailability of famotidine. 19 It is white to off-white crystalline powder, insoluble in cold water. Its solubility at 208C: 80% w/v in dimethyl formamide, 50% w/v in acetic acid, <0.01% w/v in ethanol, ethyl acetate and chloroform.…”
Section: Introductionmentioning
confidence: 99%
“…Counterions can be involved in catalysis for degradation of certain compounds [14] [15]. Different types of counterions can produce various rates of degradation.…”
Section: Effects Of Counterions and Concentrationmentioning
confidence: 99%